Enhanced bioremediation of trichloroethene-contaminated groundwater using modified γ-PGA for continuous substrate supplement and pH control: Batch and pilot-scale studies. (1st January 2021) - Luo, S.G.; Chien, C.C.; Sheu, Y.T.; Verpoort, F.; Chen, S.C.; Kao, C.M.
Abstract: In this study, the modified γ-poly-glutamic acid (m-PGA) was developed for continuous substrate supplement and pH control to bioremediate trichloroethene (TCE)-contaminated groundwater. The m-PGA was prepared by mixing γ-PGA and a stabilizer (a more sticky carbon source) [carboxymethyl cellulose, gelatin, starch, or emulsified colloidal substrate (ES)] together, which was used as a source of slow-release carbon substrate. Microcosm experiments were conducted to determine the feasibility of m-PGA for a long-term substrate releasing to enhance anaerobic TCE dechlorination. The globule diameter, viscosity, stability, adsorption and retardation effect, and zeta potential of γ-PGA mixtures were assessed. The mixture of γ-PGA and ES (volume ratio of 1:0.25) (m-PGA) had the most stable, biodegradable, long-lasting, TCE adsorption, and dispersive characteristics with a negative zeta potential (−132 mv) and uniform droplet. Up to 99% of TCE removal was achieved in microcosms with m-PGA supplement. M-PGA addition could result in an immediate TCE removal via physical adsorption and subsequent dechlorination mechanisms. In the pilot-scale study, 20 L of m-PGA was injected into an injection well to enhance TCE dechlorination. After 55 days of m-PGA injection, about 96% of TCE could be dechlorinated without byproduct accumulation. Increased ammonia concentrations were observed in microcosm and pilot-scale studies via the hydrolysis of amine from m-PGA, which could neutralize acidified groundwater. Results from the next generation sequencing indicate that strains with functions of reductive dechlorination, carbon biodegradation, B12 synthesis, and hydrogen production were detected after m-PGA injection. Highlights: M-PGA (γ-PGA + stabilizer) is a stable, degradable, and slow-releasing substrate. M-PGA causes immediate TCE removal via sorption and reductive dechlorination. Amine release from m-PGA could produce ammonia for acidification control. M-PGA caused increased TCE dechlorinators, H2 producers, and bacterial diversity.